Temporal Connectives and Their Argumentative Impact in the Story of Moses and Pharaoh in Surat Taha - المسند, د.غالية (Arts for Linguistic & Literary Studies, 2025)
This study examines the argumentative function of temporal connectives in constructing the rhetorical structure of the Quranic discourse, focusing on the story of Moses and Pharaoh in Surat Taha as a model of the conflict between truth and falsehood within a tightly ordered temporal sequence. Temporal connectives such as idha, idh, lamma, fa, thumma, and ḥatta are analyzed not only as narrative devices for organizing events but also as effective mechanisms in shaping Quranic argumentation and reinforcing persuasive logic. Through a detailed analysis of the text, the research demonstrates how these connectives contribute to sequencing events, intensifying conflict, and guiding the audience toward understanding truths and internalizing arguments. By employing an argumentative approach, the study uncovers the deeper semantic functions of these tools, showing that they transcend mere chronological markers to become instruments of rhetorical pressure and strategic direction that highlight the logic of the discourse and enhance its persuasive impact, thereby reflecting the coherence between temporal structuring and the divine message’s communicative purpose.